PELAKSANAAN KODE ETIK JABATAN NOTARIS DITINJAU DARI PROFESI NOTARIS DI KOTA YOGYAKARTA - , Nerma Novianti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The profession of notary is a noble and highly esteemed legal profession. It is said as noble profession, by reason in conducting their authority, they do not prioritize honorarium. Instead they prioritize the service to society. This authority is based and limited by Ethical Code stated by relating institution. Ethical Code of notary is a result of Extraordinary Congress in Bandung at January 27th of 2005. Ethical Code of notary gives standard and limitation of behavior to the members of organization, thus the profession of notary is still a dignified profession. Thus, this research will identify the Implementation of Ethical Code of Notary reviewed from profession of Notary in Yogyakarta City and to consider what punishment to sentence to notary in Yogyakarta city who conducted violation towards this ethical code. The research used empirical juridical approach method. The data collection and information were gained from literary research and interview. To analyze the data of research result is was conducted qualitatively. The result of this research shows that the implementation of Ethical Code of Notary Occupation in Yogyakarta City has not been entirely conducted. It seems by the existence of violation towards the conducted advertisement either by using printed media or electronic media, arrange an activity on the due of organization without any acknowledgement from concerning organization. The punishment was given to the notary who conducted violation, by shape of warning which was conducted either orally or in writing, social punishment in I.N.I organization.